CURRENT ISSUES IN DIAGNOSING THE RESPIRATORY MANIFESTATION OF GASTROESOPHAGEAL REFLUX DISEASE - Osyodlo, G.V.; Bychkova, S.A.; Katerenchuk, I.P.; Seliuk, M.M.; Kazmirchuk, A.P. (World of Medicine and Biology, 2020)
The purpose of the study was to determine the leading extraesophageal symptoms, disturbance of spirometric indices, changes in the immune system and production of nitric oxide in patients with gastroesophageal reflux disease. Bronchopulmonary manifestation of gastroesophageal reflux disease was a cough syndrome, which was characterized by the presence of non-intensive, unproductive cough with a small amount of mucous sputum and was combined, in most cases, with the hoarseness of the voice. Cough syndrome during gastroesophageal reflux disease was characterized by a lack of obstructive changes in the study of external respiration indices and elevated levels of proinflammatory cytokines in the blood serum. It was determined the higher nitric oxide content in platelets in patients with respiratory manifestations of gastroesophageal reflux disease.